1997
DOI: 10.1177/000331979704801002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple-Dose and Once-Daily Nitrate Therapy in 1212 Patients with Stable Angina Pectoris: Effects on Quality of Life Indices

Abstract: Once-daily nitrate therapy not only provides a better NYHA angina classification than multiple-dose therapy does, but also provides a better quality of life as estimated by improvement of mobility and distress indices, the most important indicators of quality of life in this category of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A complexidade da terapia, o número de comprimidos e o número de tomadas diárias são citados constantemente na literatura como fatores de interferência na adesão [15][16][17][18] , o que não se observou no presente estudo. É possível que a homogeneidade da amostra quanto ao número de comprimidos e número de tomadas não tenha permitido a expressão de diferenças quanto à adesão.…”
Section: Resultados Adesão Ao Tratamentounclassified
“…A complexidade da terapia, o número de comprimidos e o número de tomadas diárias são citados constantemente na literatura como fatores de interferência na adesão [15][16][17][18] , o que não se observou no presente estudo. É possível que a homogeneidade da amostra quanto ao número de comprimidos e número de tomadas não tenha permitido a expressão de diferenças quanto à adesão.…”
Section: Resultados Adesão Ao Tratamentounclassified
“…With particular reference to oral nitrate dosing, a study in which 31 patients were randomised to receive either MR ISMN 60 mg once daily or ISMN 20 mg twice daily for 12 weeks revealed no significant differences in compliance rates, efficacy or tolerability between the two groups ( 14). Those studies where once daily regimens purport to show a clinical benefit over twice‐daily dosing, such as Neimeyer and colleagues ( 15), often fail to indicate whether asymmetric dosing schedules were strictly employed. Furthermore, studies where quality of life indices are utilized often appear to show positive quality of life benefits without objective evidence of reduced angina pain scores or reduced rescue nitrate therapy use.…”
Section: Discussionmentioning
confidence: 99%
“…[36] It has been demonstrated that nitrate treatment provides control of angina symptoms and improves the quality of life. [7] But a major limitation of using nitrates is the development of tolerance, defined as the loss of hemodynamic and antianginal effects during sustained therapy. [8,9]…”
Section: Introductionmentioning
confidence: 99%